Práticas informacionais, desinformação e política : uma análise voltada aos docentes de pós-graduação stricto sensu em Ciência da Informação do Brasil - Santos, Júlia Schettino Jacob dos (2024)
Disinformation has had a negative impact on various spheres of people's lives, potentially influencing decision-making regarding social, political, ideological, health issues, among others. Information literacy has often been approached as a way of contributing to subjects' reflexivity, proposing a critical analysis of the production, appropriation and sharing of information in various media and formats. In this context, it is believed that studies of information practices can provide an understanding of aspects of disinformation from the perspective of the subjects themselves, taking into account their contexts and daily lives. The general objective of this study is to investigate the information practices of postgraduate professors in Information Science in Brazil at the master's and doctoral level, especially with regard to the way they deal with disinformation about politics. The specific objectives are to: a) identify how teachers use and share information about politics in their daily lives; b) analyze how the academic, professional and social context of teachers interferes with their perceptions of the Brazilian political scenario; c) verify how misinformation impacts the information practices of teachers with regard to political issues. This is an exploratory research with a qualitative-quantitative approach in which semi-structured interviews were carried out with seven teachers who teach courses on disinformation and/or information literacy. Data analysis occurred through content analysis proposed by Laurence Bardin. It was found that teachers use and disseminate information about politics as a way of problematizing reality, bringing true information and misinformation about politics to the classroom in order to encourage students' reflexivity. It was noted that the perception (positive or negative) of teachers about governments is directly related to government actions in the educational field. Furthermore, it was identified that misinformation with a “political” theme has been increasingly addressed and discussed by teachers and students included in PPGCIs. It is believed that the research contributed to the studies of information practices, correlating aspects of disinformation, politics and information literacy